Potencial antibacteriano de enterocinas em células planctonicas e em biofilme de Salmonella Typhimurium e sorotipos de Escherichia coli - Tosoni, Natara Fávaro (2019)
Escherichia coli and Salmonella Typhimurium are bacteria that present risks to human health, being able to form biofilms on abiotic surfaces, constituting an important source of contamination in the food industry, and an alternative for their control are the bacteriocins, because they are able to eliminate bacteria through the formation of pores in the cellular membrane. The objective of this study was to evaluate the action of bacteriocins produced by Enterococcus in planktonic cells and biofilm cells formed by Salmonella and sorovars Escherichia coli. Cell-free supernatant (CFS) containing enterocin produced by 3 Enterococcus isolates (MF2, MF5 and L3) were used in the plate antagonism test. Subsequently, the enterocin was tested in formed biofilm, being measured by the biomass measurement after application of violet crystal. The synergistic action among the enterocins was verified by the construction of a response surface by mixing planning. All Enterococcus isolates tested have more than two genes for expression of enterocin. The crude CFS containing enterocin showed inhibition against the indicator bacteria at all times of contact tested (6h and 18h). The enterocin expressed by the L3 isolate showed the best inhibition profile on planktonic cells. In the biofilm, the best time of inhibition occurred in the time 18h. The response surface for the synergism test showed that there was small synergistic binary interaction between the CFS MF2 and MF5 against one of the pathogens. The results show that the enterocins produced by these lactic acid bacteria (BAL) have potential for use as preservatives in foods, since the action spectrum also encompasses Gram negative bacteria in contrast to nisin, which is currently used.